Settling down spiritually: Chinese Malaysian's worship of Datuk Gong - Chin, Yee Mun; Lee, Yok Fee (Universiti Putra Malaysia Press, 2014)
When the Chinese migrated to Malaya en masse in the 19th century, they brought along with them their religious belief. Many aspects of the Chinese Religion are still maintained and practiced by the Chinese in Malaysia today. However, after years of interaction with people from other ethnic origins in Malaysia, the Chinese has synthesized local elements into their belief system. Empirically, the worship of Datuk Gong is one of them. The worship originated from the Datuk Keramat cult, which was popular among the Malays in Malaysia. This paper attempts to explain why the Chinese in Malaysia accepted local elements such as the worship of Datuk Keramat into their religion and the meaning of such acceptance. When the Chinese Malaysian transfigured certain elements found in their religion to accept the concept of Datuk Keramat, it shows their long-term commitment to make Malaysia their home. In order to achieve these objectives, observations and interviews at ten Datuk Gong temples in Peninsular Malaysia were made to collect relevant data. Data gathered shows the Chinese have transfigured their religious practice to facilitate their adaptation to live in a country, which was once foreign to them.